Knowledge and Role of Midwives in Using Maternal and Child Health Books: Pengetahuan dan Peran Bidan dalam Penggunaan Buku Kesehatan Ibu dan Anak (KIA) - Pani, Widya; Hasnawati, Hasnawati (Poltekkes Kemenkes Palu, 2023)
Background The use of KIA books by midwives in Parigi Moutong Regency has not been optimal at around 82.1%, while those who do not use KIA books as much as 17.9% are due to the fact that at all times there is always a revision of the KIA book and there is no training in filling KIA books, only socializing Zoom Meetings and YouTube Channels, so many midwives still do not understand about filling it out, especially in the mother's section of the book. The purpose of this study is to determine the relationship between midwife's knowledge and the role of midwives in the use of KIA Books. The method is Cross cross-sectional approach, the population in this study is all Midwives in the Parigi Moutong Regency Area. The sample amounted to 83 respondents. The instrument used is a questionnaire—univariate and bivariate data analysis with a chi-square test. The study's results found that some respondents were well knowledgeable, 77 people (92.8%) and had good roles totaling 81 people (97.6%). With a p-value of ≤ 0.05 which is 0.004. The conclusion is that there is a relationship between midwives' knowledge and the role of midwives in the use of KIA Books in the Parigi Moutong Regency Area. It is expected for health workers, especially midwives, to motivate mothers more in terms of using KIA books.